Determining the comprehensibility and acceptability of phonological varieties of Filipino-English as used in academic lectures - Sarile, Angela Feredo (1986)
This study conducted in an attempt to determine the comprehensibility and acceptability of phonological varieties of Filipino-English as used in academic lectures. The study concludes that the phonological and prosodic features of selected Filipino-English varieties generate certain evaluative reactions toward such varieties.